Organizational Confidence Among The Female Principals Of Secondary Schools In Dammam And Its Relationship With The Female Teachers’ Job Satisfaction - Shammaa Abdulrahman Al-Hamad; Ahmed Sulaiman Bani Murtadha (Migration Letters, 2024)
The study aimed to identify the level of organizational confidence among the female principals of secondary schools in Dammam and the level of teachers’ job satisfaction from the point of view of female teachers in public secondary schools in Dammam and to reveal the relationship between them, and to search for any differences attributed to both variables of Years of service and educational qualification. To achieve the study’s objectives, the correlational descriptive survey approach and the questionnaire tool were used to collect data. The study population consisted of all (1280) female teachers of the public secondary schools in Dammam. A simple random sample of (296) female teachers was used to apply the questionnaire. The data were statistically processed using the Statistical Packages for Social Sciences (SPSS) in light of the study questions. The study revealed a set of results, most notably: The level of organizational confidence among female principals of public secondary schools in Dammam, as perceived by female teachers, is at a (high) level for the axis as a whole, with a mean of (3.66). The dimensions are as follows: First, there is the dimension of information availability, followed by innovation opportunities, self-realization, dominant organizational values, and administrative policies. The level of job satisfaction among[1] female teachers at public secondary schools in Dammam, as perceived by them, is at a (high) level for the axis as a whole, with a mean of (3.50). The dimensions order is as follows: The dimension of the job, then the dimensions of direct management and supervision, professional growth and career progression, salary, and financial incentives. The results revealed a statistically significant positive correlation at the significance level (α ≤ 0.05) between the organizational confidence of their female principals; and their level of job satisfaction. Based on the findings, several recommendations and proposals were made.